The Milk Income Loss Contract Program for Dairy Producers - Albert de Vries (EDIS, 2005)
The Milk Income Loss Contract (MILC) Program financially compensates dairy producers when domestic milk prices fall below a specified level. The program is authorized by the 2002 Farm Security and Rural Investment Act and has no set funding level. Eligible dairy producers are those who, anytime from December 1, 2001, to September 30, 2005, commercially produce and market cow milk in the United States or produce milk in the United States and commercially market the milk outside the United States. The USDA Farm Service Agency (FSA) administers the program. This document is AN152, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 1, 2004.